Consideration for Rare Diseases in the Context of Drug Reimbursement Processes - Gosain, Sheena (Université d'Ottawa / University of Ottawa, 2015)
The aims of this thesis were to identify whether justification can be provided for the specialized consideration of drugs for rare diseases (DRDs) within reimbursement decision-making, to understand the processes applied for making coverage decisions for DRDs, and to identify how funding outcomes may differ based on the evaluation process used. The characteristics of DRDs were considered in the frame of developing an ethically acceptable rationale for the differential consideration of DRDs within coverage decision-making. The results revealed that the differing evidence base might provide ethical justification for a specialized process, but this does not justify the use of differential funding criteria. A review of processes applied internationally and within Canadian provinces and territories demonstrated that 13 out of 59 processes consider DRDs distinctively. Finally, two case studies of DRDs, Alglucosidase alfa and Canakinumab, were considered to provide insight into the application of different drug reimbursement processes and associated funding outcomes. The results highlight the heterogeneity in funding outcomes for DRDs, which arises through the application of different funding outcomes. While currently processes exist for the evaluation of DRDs and drugs in general, limitations exist with current approaches. Processes should aim to be fair and jurisdictions should carefully consider the justification underpinning a dedicated process for DRDs.